2021
DOI: 10.1186/s43066-021-00125-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of cytokeratin 19 as a diagnostic and prognostic marker in patients with HCV-related hepatocellular carcinoma

Abstract: Background The heterogeneous nature of human hepatocellular carcinoma (HCC) impedes both treatment strategies and prognostic predictions. Several markers have been proposed for the diagnosis of HCC. Cytoskeleton-associated proteins have been known as cellular integrators in neoplasm formation. Hepatic progenitor cells are thought to express alpha-fetoprotein (AFP) and hematopoietic as well as biliary markers such as cytokeratin 19 (CK 19) and cytokeratin 7. The aim of this study was to verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…CK-19 is an HCC-cancer stem cell marker that plays an integral role in carcinogenesis, metastases, and recurrence (16) . In El Raziky et al (13) study although there was no significant difference in baseline serum CK-19 levels among the three groups, its combination with AFP improved their sensitivity to 93.9% that came in harmony with our results.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…CK-19 is an HCC-cancer stem cell marker that plays an integral role in carcinogenesis, metastases, and recurrence (16) . In El Raziky et al (13) study although there was no significant difference in baseline serum CK-19 levels among the three groups, its combination with AFP improved their sensitivity to 93.9% that came in harmony with our results.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly El Raziky et al (13) , found that there was no significant difference between all groups before any intervention regarding the CK-19 levels.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations